A rare case of neonatal dwarfism - Answer - Manuela Gallo; Valentina Ibba; Lucrezia Giua Marassi; Luisa Anedda; Maria Antonietta Marcialis; Maria Cristina Pintus (Hygeia Press di Corridori Marinella, 2022)
We show a case of thanatophoric dysplasia (TD), in which the diagnosis was allowed by the identification of pathognomonic aspects at physical examination and by the whole body radiography. In particular, the physical examination shows a micromelic dwarfism, with very short limbs and a length less than -4 SDs, large head with prominent frontal bulges, short neck, narrow bell-shaped chest, brachydactyly of the hands that have a trident aspect, plication, redundant skin on the arms and legs. The radiological pictures show some characteristic features: a marked enlargement of the metaphyses with "telephone receiver" curvature, pathognonomic of this form, the platyspondylia and hypoplasia of the vertebral bodies, which appear ossified, the hypoplastic pelvic bones with roof flat acetabular, the macrocranium with prominent frontal bulges, a very narrow rib cage especially in the upper and elongated portion with very thin ribs, and the pulmonary hypoplasia. In addition, prenatal ultrasound offers other elements of support for the diagnosis: a short and curved femur and the presence of polyhydramnios, detected in at least half of TD's cases. The diagnosis was then confirmed by genetic analysis, which revealed an X807C mutation of the FGFR3 gene described in patients with type 1 TD.